Prevalence of falls among adult mothers in Saudi Arabia: a cross-sectional study - Yousef M. Alshehre; Sattam M. Almutairi (BMC Women's Health, 2023)
Abstract Background The prevalence of falls among mothers (18–49 years old) in Saudi Arabia has been overlooked and understudied. Therefore, the study aimed to identify the 1-year prevalence, rate of falls, and consequent injuries among mothers in Saudi Arabia. Methods In this cross-sectional study, a self-administered online questionnaire, including sociodemographic data and questions related to the history of falls and consequent injuries during the past 12 months, was disseminated through social media in Saudi Arabia. Results A convenience sample of 986 mothers were voluntarily recruited for this study with a median age of 33 years and an interquartile range of 10 years. The 1-year prevalence of falls among mothers was 14.1 % (n = 139), and 52.5 % (n = 73/139) of the fallers experienced more than one fall. Among mothers who had experienced a fall, 25.4 % (n = 33/139) experienced a fall incident during pregnancy. The reported consequences of falls were pain in 37.4 % (n = 52/139), muscle and ligament injuries in 7.2 % (n = 10/139), and fractures in 2.2 % (n = 3/139) of participants. The study’s findings indicate that asthma and high cholesterol level predicts the risk of falls in mothers. Conclusions According to our convenience sampling, 14.1% of mothers had experienced one or more falls in the past 12 months. The increased prevalence of falls among this age group of women supports the idea that falls are not only an issue for the older adult population, but fall prevention strategies for this age range are also needed.